Viscometric Study of PC / PEG blends in THF solvent and Gamma-Rays Effect on the Viscosity of PC - M.S. Buni; W.A. Solyman; S.A. Ali (Tikrit Journal of Pure Science)
In this research the intermolecular interaction between polycarbonate (PC) and polyethyleneglycol (PEG) in tetrahydrofuran (THF) solvent was studied, at 25˚C using a dilute solution viscometry method (DSV).